IMPLEMENTATION OF THE SIREKAP PROGRAM IN PILKADA 2020 AT KPU SUKABUMI DISTRICT - Ayunda Permata Sari; Rizki Hegia Sampurna; Andi Mulyadi (DIA: Jurnal Administrasi Publik, 2024)
Indonesia is a democratic country where the supreme power is in the hands of the people. Therefore, the people of Indonesia have the right to choose who will become the people's representatives. In order to provide facilities and a place to improve the quality of service for the direct election of leaders and representatives of the people, the KPU provides a new innovation, namely by making or creating a Mobile Vote Recapitulation Information System (SIREKAP) programme. This research aims to find out how the implementation of SIREKAP is carried out in practice by the Sukabumi Regency KPU. This research uses the theory of Chales O. Jones (1996) which has 4 dimensions, namely Organisation, Interpretation, and Implementation. The research method used in this research is Qualitative Narrative. The results of this study indicate that the implementation of SIREKAP when viewed from the dimensions, organisation, interpretation and implementation according to Charles O. Jones (1996) is still not well implemented because it has not fulfilled 3 dimensions which in terms of Organisation has not fulfilled the suitability of resources, Interpretation is still not a lack of information, socialisation, and communication received by the public regarding the SIREKAP application and the application itself is constrained by high traffic which causes the failure of sending C1 plenary results.